New insights into the epidemiology of non-Hodgkin lymphoma and implications for therapy. Issue 5 (May 2015) - Chihara, Dai; Nastoupil, Loretta J; Williams, Jessica N; Lee, Paul; Koff, Jean L; Flowers, Christopher R
<x xml:space="preserve">Abstract</x> Non-Hodgkin lymphoma (NHL) comprises numerous biologically and clinically heterogeneous subtypes, with limited data examining the risk factors for these distinct disease entities. Many limitations exist when studying lymphoma epidemiology; therefore, until recently, little was known regarding the etiology of NHL subtypes. This review highlights the results of recent pooled analyses examining the risk factors for NHL subtypes. We outline the heterogeneity and commonality among the risk factors for NHL subtypes, with proposed subtype-specific as well as shared etiologic mechanisms. In addition, we describe how the study of lymphoma epidemiology may translate into prevention or therapeutic targeting as we continue to explore the complexities of lifestyle and genetic factors that impact lymphomagenesis.